Study on font preferences of native and non-native speakers in a virtual reality environment - Zhang, Huidan; Sakamoto, Daisuke; Ono, Tetsuo (Frontiers in Virtual Reality, 2025)
IntroductionWith the growing use of virtual reality (VR) in areas like education and digital reading, understanding the factors that impact legibility in these environments is crucial. While traditional screen legibility has been extensively studied, the transition to VR requires reevaluation, especially when considering different languages and the distinction between native and non-native speakers.MethodThis study explores font preferences in VR for Chinese, Japanese, and English, focusing on font weight, style, complexity, and viewing distance. Additionally, we employed cross-linguistic VR-based experiments with quantitative assessments and qualitative interviews.ResultOur findings reveal that font preferences are influenced by a combination of language familiarity (native/non-native), viewing distance, and character complexity (glyph). Therefore, serif fonts enhance the legibility of complex logographic characters at close distances, whereas sans-serif fonts are more effective for alphabetic scripts, particularly at longer viewing distances. Moreover, when processing unfamiliar languages, users tend to shift their evaluation criteria from focusing primarily on legibility to a more balanced assessment that also incorporates aesthetic appeal.DiscussionThese insights underscore the importance of adaptive typographic strategies in VR, offering evidence-based guidelines that can enhance both legibility and user experience for a diverse global audience.